Re-examining the Benefits of Decentralization for Infrastructure Delivery at the Metropolitan Municipal and District Assemblies (MMDAs) in Ghana - Hackman, Joe Kingsley; Ayarkwa, Joshua; Osei-Asibey, Dickson; Adjei-Kumi, Theophilus; Kissi, Ernest (Advances in Social Sciences Research Journal, 2021)
Decentralization has been promoted to reflect citizens’ preferences and to improve local services. Hence, the strong demand for decentralization across the globe particularly in developing countries. This paper aimed at re-examining the benefits of decentralization for infrastructure delivery at the MMDAs in Ghana. Quantitative research approach was adopted for the study. A questionnaire survey was conducted to solicit construction professionals’ opinions on the benefits of decentralization to the MMDAs. A total of 121 professionals from 36 MMDAs in the Greater Accra and Ashanti regions of Ghana participated in the survey. Mean score ranking and Factor analysis were the statistical tools employed for the analysis of the data collected. The findings of the study indicated five categories of the benefits of decentralization including: Decentralized/Democratic governance; Equal distribution of infrastructure; Improved Local capacity; Improved Financial capacity; and Improved Local development. Furthermore, the top four significant benefits accruing from decentralization as agreed upon by the respondents were: Enhanced democratic governance; Improved internally generated funds; Utilization of local materials and Improved and faster infrastructure delivery. The findings of this study provide a wider and improved understanding of the benefits of decentralization particularly to the MMDAs, which in turn would enhance their delivery of infrastructure. Therefore, effective measures should be put in place in order to drive the implementation of decentralization in Ghana. Also, proper decentralized governance systems need to be established to improve the capacity of the MMDAs to deliver infrastructure.